2011
DOI: 10.1371/journal.pone.0026419
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyfasudil-Mediated Inhibition of ROCK1 and ROCK2 Improves Kidney Function in Rat Renal Acute Ischemia-Reperfusion Injury

Abstract: Renal ischemia-reperfusion (IR) injury (IRI) is a common and important trigger of acute renal injury (AKI). It is inevitably linked to transplantation. Involving both, the innate and the adaptive immune response, IRI causes subsequent sterile inflammation. Attraction to and transmigration of immune cells into the interstitium is associated with increased vascular permeability and loss of endothelial and tubular epithelial cell integrity. Considering the important role of cytoskeletal reorganization, mainly reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…Fasudil is a potent Rho-associated protein kinase (ROCK) inhibitor [8,9,10,11,12,13] and vasodilator and has been used for the treatment of cerebral vasospasm [9] and many other diseases, such as cancer [14,15], allergy [16] and inflammation [17,18]. The systematic administration of Fasudil was reported protecting mice from experimental autoimmune encephalomyelitis (EAE) and shifting macrophages from M1 to M2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Fasudil is a potent Rho-associated protein kinase (ROCK) inhibitor [8,9,10,11,12,13] and vasodilator and has been used for the treatment of cerebral vasospasm [9] and many other diseases, such as cancer [14,15], allergy [16] and inflammation [17,18]. The systematic administration of Fasudil was reported protecting mice from experimental autoimmune encephalomyelitis (EAE) and shifting macrophages from M1 to M2 [19].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with AHF have increased circulating levels of norepinephrine, renin and aldosterone, and lowering these neurohormones during 1 to 3 days with vasodilator and diuretic therapy has been associated with improved hemodynamics and outcomes. 37 Indeed, quiescence of neurohormonally mediated vascular inflammation may be reflected by reduced serum creatinine, 38,39 although clinical studies in resistant hypertension have shown no improvement in renal function with renal sympathetic denervation. 40 Whether this pathophysiologic link is present in AHF remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…21 To evaluate the possible relationship between Klf4 and these molecules, we determined the expression of these proteins in Klf4 cKO and control mice. Results showed that Hmox1 expression was increased by renal I/R injury and that I/R injuryinduced Hmox1 expression was unaffected by fluvastatin ( Figure 7, A and B).…”
Section: Inflammatory Cell Accumulation and Expression Of Cell Adhesionmentioning
confidence: 99%